2014
DOI: 10.1590/1982-0194201400013
|View full text |Cite
|
Sign up to set email alerts
|

Infection, local reaction and poor fixation of dressings for central venous catheter

Abstract: Objective: To identify factors related to the occurrence of infection, local reaction and poor fixation of dressings for central venous catheters. Methods: Randomized clinical trial conducted with adult patients using central venous catheter for short periods, hospitalized in intensive and semi-intensive care units of a university hospital. Results: 85 patients (43 chlorhexidine dressings; 42 gauze and tape). Use of blood component increases the chance of catheter-related infection; use of dressings for more t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 2 publications
(1 reference statement)
0
7
0
1
Order By: Relevance
“…A more recent publication (Pedrolo et al . ) suggests that using dressings with gauze and microporous tape increases the probability of causing a local reaction, consequently facilitating the proliferation of local microbiota and increasing the risk of infectious complications. Another study from Australia revealed the benefits of keeping the exit‐site free from a dressing during healing to avoid further skin irritation (Lily et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more recent publication (Pedrolo et al . ) suggests that using dressings with gauze and microporous tape increases the probability of causing a local reaction, consequently facilitating the proliferation of local microbiota and increasing the risk of infectious complications. Another study from Australia revealed the benefits of keeping the exit‐site free from a dressing during healing to avoid further skin irritation (Lily et al .…”
Section: Discussionmentioning
confidence: 99%
“…Pedrolo et al . () in a randomised controlled clinical trial on central venous catheter dressings, found that polyurethane material dressings presented greater drainage accumulation at the exit‐site as they have no absorption capacity. Furthermore, the research involving a series of cases using polyurethane dressings on central venous catheters demonstrated a greater susceptibility to cutaneous toxicity and thermal barrier, factors that may be linked to an increased number of infections (Silveira et al .…”
Section: Introductionmentioning
confidence: 99%
“…15 Regarding the dressing adhesiveness, a study showed that the time of permanence of the catheter over 5 days increases the risk of poor fixation of the dressing in more than five times and the risk of development of local reaction by the use of occlusive dressing in continuous contact with the skin in more than four times. 28 In this context the literature shows a study describing that nonintact dressings increase the proliferation of microorganisms at the insertion site. 2,29 Therefore daily inspection and palpation to verify the integrity, adhesiveness, and saturation of chlorhexidine-impregnated gel dressings, as well as reviewing the need for maintaining the CVC, are essential strategies to ensure the safety of patients by preventing catheter-related infections.…”
Section: Frequency Of Change Of Chlorhexidine-impregnated Gel Dressingsmentioning
confidence: 99%
“…28 Inadequate fixation results in spontaneous detachment of the dressing, a factor the leads to its change. 28 The dressing is intended to be occlusive, therefore it should be maintained totally fixed to the skin of the patient to protect the insertion site of the catheter, provide stability to the device, and reduce the risk of contamination by microorganisms.…”
mentioning
confidence: 99%
See 1 more Smart Citation